2020
DOI: 10.1111/gcb.15074
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and challenges of micro/nanoplastics‐induced toxicity with special reference to phytotoxicity

Abstract: Plastic pollution has become a global concern for ecosystem health and biodiversity conservation. Concentrations of plastics are manifold higher in the terrestrial system than the aquatic one. Micro/nanoplastics (M/NP) have the ability to alter soil enzymatic system, soil properties and also affect soil borne microorganisms and earthworms. Despite, the knowhow regarding modulatory effects of plastics are acquired from the study on aquatic system and reports on their phytotoxic potentials are limited. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 83 publications
0
38
0
Order By: Relevance
“…Owing to the long-term persistence of plastics in the environment, their accumulation is one of the most widespread and long-lasting anthropogenic changes to the Earth's surface. Once in the environment, large plastic debris gradually degrades into smaller pieces through weathering and other disintegration processes [2][3][4][5], which can further increase their dispersion and incorporation into the soil [6][7][8]. Microplastics are generally defined as plastic particles with diameters less than 5 mm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the long-term persistence of plastics in the environment, their accumulation is one of the most widespread and long-lasting anthropogenic changes to the Earth's surface. Once in the environment, large plastic debris gradually degrades into smaller pieces through weathering and other disintegration processes [2][3][4][5], which can further increase their dispersion and incorporation into the soil [6][7][8]. Microplastics are generally defined as plastic particles with diameters less than 5 mm [9].…”
Section: Introductionmentioning
confidence: 99%
“…MPs and NPs change soil properties and bacterial communities. Rhizobia can potentially change with changes in the soil matrix [166]. The ingestion of MPs by soil organisms could influence bacterial diversity; e.g., Zhu et al reported that in the collembolan gut, MPs potentially enhanced bacterial diversity, possibly due to a move in feeding after MP exposure [102].…”
Section: Interaction With Soil Microbesmentioning
confidence: 99%
“…Following the NPs diffusion in the environment, all animal species can be involved in a direct way by ingestion and through the bio-magnification [19]. The plant kingdom is also included within the study because it is closely related to soil pollution [111,112] therefore sampling biological matrices to understand dose-effects of NPs is fundamental for wildlife safeguard.…”
Section: Biologicalmentioning
confidence: 99%
“…They can also interact with membrane proteins and transport of ions. The main ways through which NPs and plant can interact are: cell wall and cuticle by passive transport; proteins on the membrane by diffusion facilitated; endocytosis; plasmodesmata by intercellular translocation; stomata [111]. Laboratory test exposure of plants to NPs has basically the same procedure as animals.…”
Section: Biologicalmentioning
confidence: 99%